ANALYSIS OF OUTRIGGER STRUCTURAL SYSTEM FOR HIGH-RISE BUILDING SUBJECTED TO EARTHQUAKE LOADS - V. BHARGAVI; MUPPIDI SANTHI DEVI (International Journal of Innovations in Engineering Research and Technology, 2021)
Designing a high rise building has its challenges. Different structural systems have been developed to control the lateral displacement of high rise buildings. One of these systems is called the outrigger which decreases both the horizontal movement of the structure and the moment on the foundation of the structure. However the location of the outriggers has an immense influence on the efficiency of the structure. Outrigger optimization is a significant challenge. The objective of this thesis is to give a better understanding of outrigger locations and its efficiency of each outrigger when several outriggers are used in the structure and the behavior of outriggers. Tall building development has been rapidly increasing worldwide introducing new challenges that need to be met through engineering judgment. In modern tall buildings, lateral loads induced by wind or earthquake are often resisted by a system of coupled shear walls. But when the building increases in height, the stiffness of the structure becomes more important and introduction of outrigger beams between the shear walls and external columns is often used to provide sufficient lateral stiffness to the structure. The outrigger structural system is commonly used to control the excessive drift due to lateral load, so that, during small or medium lateral load due to either wind or earthquake load, the risk of structural and nonstructural damage can be minimized. For high-rise buildings, particularly in seismic active zone or wind load dominant. In this study two structural systems were considered, moment resisting frame system (bare frame) and outrigger structural system (with four configurations). A 40 story high rise building is modeled and performed analysis in ETABS 2017 software for all models and the results were compared in terms of lateral displacement, story drift and base shear.